1994
DOI: 10.1088/0953-8984/6/49/003
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering in CuInS2xSe2(1-x)mixed crystals

Abstract: Raman spectra of CulnSwSe(l-,, mixed crystals are reponed. The dependence of the mode frequencies on lhe composition is studied. Two-mode behaviour is observed for the higherfrequency phonons. One-mode behaviour is found for the low-frequency modes corresponding to the zone-edge acoustic phonons of zincblende.Solid solutions of CuInSbSez(l-z) type are considered as an alternative for CuInSe;? as an absorber in thin-film solar cells [l]. They crystallize in the chalcopyrite structure over the whole composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…This mode is observed at 174 cm -1 in CuInSe 2 and 184 cm -1 in CuGaSe 2 [15], and shifts in an approximately linear fashion in CuIn y Ga y-1 Se 2 alloys with the A1(Se-Se) peak position following 174 + 12.9y [14]. In Ga-free alloys with sulfur, CuIn(S x Se x-1 ) 2 , it is observed that the A1(Se-Se) peak shifts to higher frequencies and reduces in intensity with increasing x [16,17]. At the same time, the sulfur related A1(S-S) mode observed in pure sulfide CIS at 290 cm -1 increases in intensity relative to the A1(Se-Se) mode.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This mode is observed at 174 cm -1 in CuInSe 2 and 184 cm -1 in CuGaSe 2 [15], and shifts in an approximately linear fashion in CuIn y Ga y-1 Se 2 alloys with the A1(Se-Se) peak position following 174 + 12.9y [14]. In Ga-free alloys with sulfur, CuIn(S x Se x-1 ) 2 , it is observed that the A1(Se-Se) peak shifts to higher frequencies and reduces in intensity with increasing x [16,17]. At the same time, the sulfur related A1(S-S) mode observed in pure sulfide CIS at 290 cm -1 increases in intensity relative to the A1(Se-Se) mode.…”
Section: Introductionmentioning
confidence: 89%
“…The ratio of the A1(S-S) and A1(Se-Se) modes correlates with the of the relative S/Se content in the CISSe material [17]. It is observed that the 290 cm -1 peak does not shift when alloying with different S/Se ratios, but this peak vanishes for low values of x [16]. It should be kept in mind that this is the behaviour seen in homogeneously mixed CuIn(S,Se) 2 crystals.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this case, the A 1 mode of the CuIn͑S,Se͒ 2 quaternary presents a bimodal behavior, with two bands involving pure S-S and Se-Se vibrations. 16 shown in Fig. 5, the Raman spectra are characterized by a dominant peak corresponding to the S-S vibrational mode, which indicates that S atoms have almost totally replaced the Se atoms in the crystalline lattice of the chalcopyrite phase, the percentage of remaining Se atoms being of the order of x Յ 5%.…”
Section: B Sulfur Annealed Filmsmentioning
confidence: 97%
“…In principle, the main peaks in the Raman spectra from CuIn͑S,Se͒ 2 correspond to the A 1 symmetry zone-center phonon band of the chalcopyrite structure that shows a bimodal behavior with two bands involving pure S-S and Se-Se vibrations. 5 The spectra measured in the samples are characterized by a dominant peak, which corresponds to the S-S vibrational mode. The position of this band is close to the reference position obtained from a CuInS 2 single crystal ͑290 cm −1 ͒.…”
Section: B Raman/aes Measurementsmentioning
confidence: 99%